Taʿlīm al-Lughah al-ʿArabiyyah fī al-Madrasah al-Ibtidāʾiyyah al-Islāmiyyah (Dirāsah Maydāniyyah fī Madrasah Harapan Bunda al-Ibtidāʾiyyah al-Islāmiyyah, Purwokerto) - ade Ruswati (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2016)
Arabic language instruction at Harapan Bunda Integrated Islamic Elementary School in Purwokerto serves as a fundamental component in preparing students for their future academic and personal development. It plays an important role in nurturing learners with Qur’anic values and moral character. The school's Arabic program also supports students in gradually understanding the vocabulary of the Qur’an through the implementation of a specialized Arabic language curriculum. This study aims to examine the implementation of Arabic language teaching at Harapan Bunda Integrated Islamic Elementary School in Central Java, Indonesia, identify the challenges encountered in both teaching and learning, and analyze how the current curriculum facilitates students’ vocabulary memorization. In addition, the study investigates the extent of students’ comprehension of the instructional materials and explores the major issues affecting the effectiveness of Arabic language education in the school.